Does Microfinance Make Households More Resilient to Shocks? Evidence From the Cyclone Phailin in India. (21st August 2017) - Calis, Thijmen; Gangopadhyay, Shubhashis; Ghosh, Namrata; Lensink, Robert; Meesters, Aljar
Abstract: This research note examines the relevance of microfinance as a means to cope with natural disasters, using the event of the cyclone Phailin, which struck India in 2013. The results indicate that microfinance helps reduce the negative effects of extreme weather‐related shocks. In light of the somewhat disappointing outcomes suggested by several recent rigorous impact studies, this research paints a more positive picture of the importance of microfinance as an insurance mechanism to deal with weather‐related risks. Copyright © 2017 John Wiley & Sons, Ltd.